2020
DOI: 10.1002/glia.23788
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells: Rescuers of central demyelination

Abstract: The presence of peripheral myelinating cells in the central nervous system (CNS) has gained the neurobiologist attention over the years. Despite the confirmed presence of Schwann cells in the CNS in pathological conditions, and the long list of their beneficial effects on central remyelination, the cues that impede or allow Schwann cells to successfully conquer and remyelinate central axons remain partially undiscovered. A better knowledge of these factors stand out as crucial to foresee a rational therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Thus, the negative effect of tamoxifen on Schwann cell‐derived remyelination might be secondary to the positive effect on oligodendrocytes and OPCs. Further, Schwann cell‐derived remyelination is highly influenced by prevention of migration as well as inhibition of differentiation in favor of oligodendrocytes by reactive astrocytes ( 70 ). The present results show that in TMEV‐IDD, the phenotype of astrocytes is influenced in the progression of lesions, but not by TOG application.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the negative effect of tamoxifen on Schwann cell‐derived remyelination might be secondary to the positive effect on oligodendrocytes and OPCs. Further, Schwann cell‐derived remyelination is highly influenced by prevention of migration as well as inhibition of differentiation in favor of oligodendrocytes by reactive astrocytes ( 70 ). The present results show that in TMEV‐IDD, the phenotype of astrocytes is influenced in the progression of lesions, but not by TOG application.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the growth of neurites, the synchronous migration of SCs is also crucial for the repair of peripheral nerve injury. [43][44][45][46] The migration of SCs from the DRG spheres along the direction of fibers and the aligned neurites after culturing for 7 days on the microfibrous architectures with different fiber spacings were characterized as shown in Figure 7. SCs derived from the DRG spheres were found to tightly attach and wrap around the regenerated neurites in a linear end-toend manner.…”
Section: Ehd-printed Microfibrous Architectures With Cell-scale Spaci...mentioning
confidence: 99%
“…Many preclinical studies have shown that SCs obtained via in vitro culture methods form a bridge across a lesion site, recruit endogenous SCs, promote axon growth and sparing, and provide a new myelin sheath to regenerated and demyelinated axons in the PNS [ 16 , 120 , 121 ] and CNS [ 10 , 14 , 118 ]. SCs do not naturally reside in the CNS but cells with SC characteristics can be found within traumatic and demyelinating lesions in the brain and the spinal cord [ 122 ].…”
Section: Sc Cultures In Translational Researchmentioning
confidence: 99%
“…For instance, SCs can be isolated from assorted mouse models [ 13 ] and transgenic animals expressing gene reporters. In this way, researchers have been able to compare cell behavior in vitro and in vivo, and trace the fate of transplanted SCs to grasp the associated mechanisms of repair, migration and myelination in central and peripheral nerve lesions [ 10 , 14 , 15 , 16 ]. A particular advantage of SCs is that it is possible to manufacture them at a large scale from human autologous tissues following guidelines compatible with safe manufacturing practices, which has made it possible to re-implant cultured SCs for therapeutic benefit in human patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%